Employee performance under organizational culture and transformational leadership: A mediated model - Rahmat Al Amin; Wawan Prahiawan; Agus David Ramdansyah; Didit Haryadi (Institute of Computer Science (IOCS), 2023)
Among effective management systems, the importance of human resources is increasing. Employee performance is one of the most important factors affecting success. Therefore, human resource management in an organization has become one of the most critical functions of a company. The purpose of this study is to determine the variables that affect employee performance and develop a basic theoretical model and a research model. This study uses an associative descriptive quantitative method with a sample of 152 respondents who are employees of PT PLN Cilegon Managing Unit. Improving employee performance can be done by adjusting and upholding the application of organizational cultural values. To be able to improve employee performance can be done by increasing transformational leadership. Enhancing corporate culture can be done by adjusting and upholding the application of organizational cultural values. To be able to improve employee performance can be done by increasing work motivation. This research is expected to provide a theoretical contribution to the literature in the context of human resource management.